Exploring the effects of exercise on T cell function and metabolism in cancer: a scoping review protocol - Low, J. L.; Lee, H. J.; Edgett, B. A.; Romme, K.; Culos-Reed, S. N.; Lee, J. B. (Frontiers in Physiology, 2025)
BackgroundThe global burden of cancer is escalating, and improved strategies for disease prevention and treatment are needed. The immune system, particularly T cells, plays a crucial role in cancer surveillance and eradication. Immunotherapy strategies that leverage the anti-cancer T cell response have significantly advanced therapeutic approaches to cancer treatment. Exercise is a lifestyle factor that naturally stimulates and strengthens the immune system. This interaction may not only be linked to the benefits of exercise in decreasing cancer risk and increasing survival but may also have the potential to be harnessed to enhance current forms of immunotherapy. Central to the exercise-immune system axis and anti-cancer control are T cells, yet little is known about how exercise might influence their function and metabolic fitness.ObjectiveWe propose a scoping review with the aim to understand and summarize the current literature on the effects of exercise on T cell function and metabolism in cancer, identifying potential key mechanisms, impacts on therapeutic applications, exercise modalities, and associated outcomes.MethodsThis scoping review will be conducted according to the methodology for scoping reviews laid out by JBI. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR) will be followed. Experimental studies involving i) humans OR mammals and ii) examinations of T cell function and metabolism, and iii) exercise interventions, and iv) in the context of cancer will be included.ResultsData search, screening and extraction will take place from June 2025-December 2025. Preliminary searches conducted while developing the initial search strategy resulted in an estimated ∼700–1000 titles and abstracts for initial screening.Conclusion/Implications/DisseminationThe proposed scoping review will be submitted for publication upon completion. The potential findings hold profound implications for future research in this field, providing mechanistic insights into the exercise-immune system axis that can be leveraged to enhance immune-based approaches for cancer prevention, treatment, and long-term survivorship.